The Effects of Shariah Governance on Takaful Performance of Takaful Operators in Malaysia - Nurul Nazlia Jamil; Ainulashikin Marzuki (Academic Inspired Network, 2024)
Volume: 8 Issues: 59 [December, 2023] pp. 468 - 474